2000
DOI: 10.1046/j.1471-4159.2000.0741666.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cortical Extracellular Fluid Glutamate in Transgenic Mice Expressing Human Mutant (G93A) Cu/Zn Superoxide Dismutase

Abstract: Transgenic mice expressing a mutated (G93A) human Cu/Zn superoxide dismutase (SOD1) develop motor neuron pathology and clinical symptoms similar to those seen in patients with amyotrophic lateral sclerosis. Loss of motor neurons is most prominent in lumbar, followed by cervical cord and then brainstem. No significant cell death has been reported in motor cortex. The integrity of the cortical glutamate reuptake systems was evaluated using intracerebral microdialysis and western immunoblot assays for the glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Previous reports have indicated progressive reactive astrogliosis, nitrotyrosine labeling and loss of astrocytic glutamate transport in SOD1 mutant rodent models of ALS (Alexander et al, 2000;Ferrante et al, 1997;Tu et al, 1996), and a specific decrease of the GLT-1 glutamate transporter has been reported in ventral horn of the G93A rats that are the subject of this study (Howland et al, 2002). Consistent with these prior studies we see a dramatic increase in astrogliosis, as indicated by GFAP labeling, most prominent initially in ventral horn, and extending throughout the gray matter of the spinal cord by the onset of symptoms (Fig 2A, 3).…”
Section: Effects Of Nas On Glial Pathology In G93a Sod1 Transgenic Ratsmentioning
confidence: 90%
“…Previous reports have indicated progressive reactive astrogliosis, nitrotyrosine labeling and loss of astrocytic glutamate transport in SOD1 mutant rodent models of ALS (Alexander et al, 2000;Ferrante et al, 1997;Tu et al, 1996), and a specific decrease of the GLT-1 glutamate transporter has been reported in ventral horn of the G93A rats that are the subject of this study (Howland et al, 2002). Consistent with these prior studies we see a dramatic increase in astrogliosis, as indicated by GFAP labeling, most prominent initially in ventral horn, and extending throughout the gray matter of the spinal cord by the onset of symptoms (Fig 2A, 3).…”
Section: Effects Of Nas On Glial Pathology In G93a Sod1 Transgenic Ratsmentioning
confidence: 90%
“…These mice replicate much of the human ALS phenotype. They develop eventual paralysis of their hindlimbs at approximately 120 days of age subsequent to mitochondrial damage, an accumulation of extracellular glutamate and intracellular filamentous inclusions, motor neuron (MN) cell death, and loss of axons innervating the muscle [(Gurney et al 1994;Klivenyi et al 1999;Alexander et al 2000;Fischer et al 2004)]. …”
Section: Introductionmentioning
confidence: 99%
“…Kong and Xu 16 proposed two likely scenarios for the loss of motor neurons: (1) there may be an extended period of gradual presymptomatic motor neuron loss, or (2) there may be an abrupt loss of motor neurons coinciding with symptom onset. So far, studies using mice with a short disease course have shown a gradual loss of motor neurons beginning at the onset of clinical symptoms, with no prior loss in the presymptomatic stage.…”
mentioning
confidence: 99%